Financial intelligence : a manager's guide to knowing what the numbers really mean - Berman, Karen, 1962- (Harvard Business Review Press, 2013)
""Inc." magazine calls it one of "the best, clearest guides to the numbers" on the market. Readers agree, saying it's exactly "what I need to know" and calling it a "must-read" for decision makers without expertise in finance. Since its release in 2006, "Financial Intelligence" has become a favorite among managers who need a guided tour through the numbers--helping them to understand not only what the numbers really mean, but also why they matter. This new, completely updated edition brings the numbers up to date and continues to teach the basics of finance to managers who need to use financial data to drive their business. It also addresses issues that have become even more important in recent years--including questions around the financial crisis and those around broader financial and accounting literacy. Accessible, jargon-free, and filled with entertaining stories of real companies, Financial Intelligence gives nonfinancial managers the confidence to understand the nuance beyond the numbers--to help bring everyday work to a new level."--Publisher's website.